Stories of Globalization : Transnational Corporations, Resistance, and the State - Bonanno, Alessandro (Rural studies series (University Park, Pa.), 2008)
"Analyses transnational corporations, groups who resist them, and the primary context within which the relationship between transnational corporations and their opponents unfold: the state. Argues that globalization is a contested terrain in which the power of transnational corporations is affected by mounting opposition and internal contradictions"--Provided by publisher.